(3HjGf bhGYO GdLaQ GdefShHI Edi MVQI GdChdjGA hbOhI GdCUajGA CejQ GdeDefjf Ydi Hf CHj WGdH cQe Gddg hLggs
(3ChdgG (B:s
(3CeG HYO abO GdJeS efj CLd GdENhGf eef dg aj MSf GdXfhf QSGdI aj HjGf bhGYO GdLaQ GdefShH Edi MVQI SjO GdChdjGA s
(3BNQgG (B:s
(3aGdeSDd ef cQeg JjSjQ Pdc hefg GdEYGffg hGdJhajb hUdi Gddg Ydi eMeO Bdg hUMHg CLeYjf Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI GdehUd (B(300 (3L(B) s
Keywords: (3GdMQha h GdChaGbs